Testing the Dispersal-Origin-Status-Impact (DOSI) scheme to prioritise non-native and translocated species management - Tarkan, Ali Serhan; Emiroğlu, Özgür; Aksu, Sadi; Kurtul, Irmak; Błońska, Dagmara; Bayçelebi, Esra; Soto, Ismael; Chan, Samuel S; Haubrock, Phillip J; Bradshaw, Corey J A (Scientific reports, 2024)
Assessing actual and potential impacts of non-native species is necessary for prioritising their management. Traditional assessments often occur at the species level, potentially overlooking differences among populations. The recently developed Dispersal-Origin-Status-Impact (DOSI) assessment scheme addresses this by treating biological invasions as population-level phenomena, incorporating the complexities affecting populations of non-native species. We applied the DOSI scheme to the non-native and translocated species reported in a shallow alluvial lake (Lake Gala) and a reservoir (Sığırcı Reservoir) in north-western Türkiye. DOSI identified 12 established species across both ecosystems, including nine fish, two invertebrates, and one mammal. Most species received High and Medium-High priority rankings, in both sites. In contrast, Medium and Low priority rankings were less common, each occurring once in Lake Gala and four times in Sığırcı Reservoir. These high-priority species warrant targeted management interventions due to their established status, autonomous spread, and observed negative impacts. By enabling a more nuanced and context-specific approach, DOSI facilitates the development of targeted strategies for managing species posing the highest risks. Moreover, DOSI's focus on population-level assessment within ecosystems is highly relevant for stakeholders, decision-makers, and environmental managers, because it provides a more detailed and precise unit of evaluation.
Keywords: Animals; zachování přírodních zdrojů; Gymnocephalus cernua; Myocastor coypus; Lakes; Lake Gala; ryby; Invertebrates; bezobratlí; Ecosystem; zvířata; Biological invasions; Sığırcı reservoir; Introduced Species; jezera; Fishes; ekosystém; Callinectes sapidus; Biodiversity; Invasive species; zavlečené druhy; Conservation of Natural Resources; biodiverzita